2006
DOI: 10.1080/14034940600585820
|View full text |Cite
|
Sign up to set email alerts
|

Client perceptions of the performance of public and independent not-for-profit primary healthcare

Abstract: Clients of the INPO generally rated the service more positively than clients of publicly provided services. The results indicate that trust in HC depends more on a family doctor system than a service provider.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The respondents in SM and also in SWM reported better access to an appointment than those in EM and in WM and rated interpersonal quality of service higher than those in WM. The findings were consistent with the previous surveys carried out among the HC clients in 2000 and 2002 [11,22]. We believe that both the nonprofit and the public provider could organize physician services favourably.…”
Section: Discussionsupporting
confidence: 95%
“…The respondents in SM and also in SWM reported better access to an appointment than those in EM and in WM and rated interpersonal quality of service higher than those in WM. The findings were consistent with the previous surveys carried out among the HC clients in 2000 and 2002 [11,22]. We believe that both the nonprofit and the public provider could organize physician services favourably.…”
Section: Discussionsupporting
confidence: 95%
“…The willingness to outsource was higher in the municipality (SM) that had contracted out all its PHC services compared to the municipalities with limited outsourcing (EM, SWM, WM). Previous research by us showed that the service provider in SM had succeeded in developing PHC services; patients were more satisfied with PHC services and they had more trust in the services provider than in the reference municipalities [45]. In the reference municipalities the politicians had less of those experiences in outsourcing.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies of Finnish municipal organizations have shown that reductions in work force have had negative effects on the psychosocial work environment and employee health [15][16][17]. Previous studies have also shown many advantages in a family doctor system [4,18]. Furthermore, greater emphasis in SM on employee health promotion and continuing education, nurses' larger autonomy and less frequent use of contract workers might have had positive effect on the psychosocial work environment and employee health [10,19].…”
Section: Aim and Hypotheses Of The Studymentioning
confidence: 97%
“…The comparison municipalities had rehabilitation programs for the personnel but not the organizational policy to promote employee health. In SM nurses' responsibility for care was larger and the use of locum and temporary doctors on emergency duty less frequent than in the comparison municipalities [4].…”
Section: Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation